Aspiration-attainment gaps predict adolescents’ subjective well-being after transition to vocational education and training in Germany - Nießen, Désirée [Verfasser]; Wicht, Alexandra [Verfasser]; Lechner, Clemens M. [Verfasser] (My University, 2023)
“An occupational aspiration-attainment gap (AAG) is defined as a discrepancy between the socioeconomic status (SES) of the aspired occupation and the one attained. We investigated how experiencing an occupational AAG after transition to vocational education and training (VET) affects three domains of subjective well-being (SWB) among adolescents in Germany (general life, job, and income satisfaction). Using longitudinal data from the German Socio-Economic Panel (SOEP), we could track respondents’ SWB during the transition to and during VET. Results from latent growth curve models revealed that both under- and overachievement of aspirations (i.e., negative and positive AAGs) reduced initial levels of SWB after VET entry - especially work-related satisfaction (i.e., income and job satisfaction). Individuals with an AAG (both negative and positive) tended to experience a slightly larger increase in SWB during VET than those who met their aspirations. Overall, our results suggest that the decisive factor for adolescents’ SWB is not the SES of the VET position they attain, but rather whether that position is the exact type of position to which they aspired.” (authors’ abstract; BIBB-Doku)
Keywords: G 1.3.2 Bildungsverhalten und -verläufe; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; 370; 300; Bildungsaspirationen; Berufswunsch; Auswirkung; Jugendlicher; Zufriedenheit; Berufszufriedenheit